Follow Your Heart: Survival Chances and Costs after Heart Attacks—An Instrumental Variable Approach - Sanwald, Alice (Health Serv Res, 2016)
OBJECTIVE: To determine the effect of heart attack patients’ access to intensive treatment on mortality and costs. DATA SOURCES: Administrative data of 4,920 patients with acute myocardial infarction from the Austrian Social Security Database and the Upper Austrian Sickness Fund for the period 2002–2011. STUDY DESIGN: As treatment intensity in a hospital largely depends on whether it has a catheterization laboratory, we explore the effects of patients’ initial admission to such specialized percutaneous coronary intervention (PCI) hospitals. To account for the nonrandom selection of patients into hospitals, we exploit individuals’ place of residence as a source of exogenous variation in an instrumental variable framework. PRINCIPAL FINDINGS: We find that the initial admission to PCI hospitals increases patients’ survival chances substantially. The effect on 3‐year mortality is −9.5 percentage points. Subgroup analysis shows the strongest effects in relative terms for patients below the age of 65. We do not find significant effects on long‐term inpatient costs and only marginal increases in outpatient costs. CONCLUSIONS: Our findings suggest that place of residence affects the access of patients to invasive heart attack treatment and therefore their chance of survival. We conclude that that providing more patients immediate access to PCI hospitals should be beneficial.